Rol' narušenij vegetativnogo ravnovesija v razvitii patologii pri vysokich fiziceskich nagruzkach v detsko-junošeskom sporte (obzor literatury) - Ponomareva, A. G.; Krivošcapov, M. V.; Lakšin, A. M.; Mitelev, S. S.; Morozov, V. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The literature review presents modern data on the role of violations of the vegetative balance in the development of pathology at high physical activity in youth sports, using the evaluation criteria of vegetative balance in the correction of physical loads during the rehabilitation and sports, the prevention of diseases and dependencies. The article reflects the impact of environmental pollution, the state of the systems of digestion and excretion on the level of adaptation of the organism to toxic effects and shows the possibility of using herbal medicine and physical activity for recovery.